Analysis of the Distribution of Public Fuel Stations in Pati Regency Based on a Geographic Information System - Royfando, Rizqi Berlyan; Hadibasyir, Hamim Zaky; Kiat, Umar El Izzudin; Arijuddin, Basyar Ihsan (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Pati Regency is one of the largest districts in Central Java Province. This causes population density which can affect population mobility there too. The large population in Pati Regency can affect population mobility. This mobility requires fuel consumption. The provision of fuel by the government and private sector through public fuel stations is one of the most important infrastructures available. With the existence of Public Fuel Filling Stations (SPBU) the wheels of the economy will run properly.This study uses a descriptive method with a qualitative approach. The aim of this research is to examine the distribution pattern and affordability of Public Fuel Filling Stations in Pati Regency. The nearest neighbor analysis method is used to calculate the distribution pattern of location points between Public Fuel Filling Stations. Also, Buffer analysis is carried out to detect conditions around objects with a certain radius/distance. The results of the research show that the distribution of gas station locations in Pati Regency forms a cluster pattern and the distance between gas station locations is included in the very close criteria.